Testing an Online Training Session on Couples' Perinatal Sexual Changes Among Health Care Professionals and Paraprofessionals. (2nd March 2021) - de Pierrepont, Catherine; Brassard, Audrey; Lessard, Isabelle; Gingras, Anne‐Sophie; Péloquin, Katherine
Abstract : Introduction: During and after pregnancy, couples have to adapt to sexual changes. Although many couples have questions and preoccupations regarding those changes, they are rarely addressed by professionals and paraprofessionals in perinatal health care, mainly because of lack of knowledge and training. An online training session that addressed couples' perinatal sexual changes tailored for health care perinatal professionals (nurses and midwives) and paraprofessionals (doulas) was developed, implemented, and evaluated. Methods: Participants completed 4 steps: (1) a baseline online questionnaire assessing training needs and measures on knowledge, attitudes, and perceived counseling skills regarding couples' perinatal sexual changes; (2) a 2‐hour online training session on the topic with theoretical and practical content; (3) an online post‐training satisfaction questionnaire; and (4) a one‐month follow‐up assessment using the same measures as at baseline. Results: Of the 74 participants (20 nurses, 20 midwives, 34 doulas) who completed the study, 37.8% had previous training in sexuality and 18.9% in perinatal sexuality. Results showed pre‐ to post‐training significant increases in knowledge and attitudes toward couples' perinatal sexual changes, characterized by more positivity, flexibility, openness, and sense of competence regarding the topic. There were also significant pre‐ to post‐training increases in perceived utility, comfort, intention, and sense of self‐efficacy related to counseling skills regarding couples' perinatal sexual changes. After training, more participants discussed couples' sexual changes with couples during and after pregnancy. After training, significantly fewer participants reported lack of knowledge, lack of training, and lack of discomfort as barriers to discussions on couples' perinatal sexual changes, whereas more reported lack of time as a barrier. Global satisfaction with the training was high. Discussion: This training can help foster more discussions on the topic from perinatal professionals and paraprofessionals to better meet couples' needs for information and support.